THE METHODOLOGICAL APPROACH IN THE MANAGEMENT OF CONSERVATION DATA FOR STUCCO ARTIFACTS - Capasso, Filippo Edoardo; Castiello, Francesca; Dichiara, Simona; Giandomenico, Manuel; Iacopino, Natalie; Maddalena, Erika; Mauri, Camilla; Muca, Sokol; Roscigno, Mariagiulia; Schiattone, Sofia (Protection of Cultural Heritage, 2019)
Some 90 Roman stucco fragments, coming from the Archaeological Park of Herculaneum, underwent in the conservation-restoration process within the Istituto Superiore per la Conservazione ed il Restauro (ISCR) laboratories in Matera. Before the conservation activity, the wide number of this manufacts brought us to design a data management system, suitable for stucco findings. Nowadays, the international approaches towards data management of this kind of artifacts is extremely heterogeneous and the absence of an unequivocal data sheet makes the cataloguing very complex and laborious. Our studies on the fragments allowed us to draw up a specific cataloguing instrument for this kind of material, carried out with a software structuring data collection in order to respond to different necessities, such as completeness and updatability, required by an efficient data management system.